The influence of the ACTN3 R577X polymorphism in the responsiveness to post-activation jump performance enhancement in untrained young men - Guilherme Beneduzzi Mantovani; Renan Vieira Barreto; Victor Alvino de Souza; Carlos Roberto Bueno Júnior; Claudio de Oliveira Assumpção; Camila Coelho Greco; Benedito Sérgio Denadai; Leonardo Coelho Rabello de Lima (Universidade Federal de Santa Catarina, 2021)
We aimed to investigate the influence of the alpha-actinin-3 (ACTN3) R577X polymorphism on responsiveness to post-activation performance enhancement (PAPE) of countermovement jumps (CMJ) in untrained subjects. Sixteen untrained men were allocated to two groups according to their ACTN3 gene alleles: homozygous for the X allele (XX, n = 9) or homozygous for the R allele (RR, n = 7). CMJ height, mean power output and vertical force were determined twice (CMJ1 and CMJ2) in two conditions: control (CON) and potentiated (PAPE). In the CON condition, CMJ were performed before and after 15 min of rest. In the PAPE condition, CMJ were performed 15 min before and 4 min following five squats with a 5-repetition maximum (5RM) load. Different conditions were performed on separate days in a randomized order. For statistical analysis three-way ANOVAs were used to compare the differences between conditions (CON and PAPE), time (CMJ1 and CMJ2) and groups (XX and RR). The level of significance was set at p < 0.05. Effect sizes were calculated as Cohen's d. The effect sizes for changes in CMJ height for CON and following pre-activation for PAPE were 0.04 and 0.08, respectively. No significant differences were found for CMJ height between XX and RR at baseline (1.07 ± 2.54 cm e -0.82 ± 2.56 cm, respectively). No differences were found (p>0.05) in responsiveness to PAPE between groups (XX = -0.20 ± 1.6 cm and RR = -0.81 ± 2.7 cm). We conclude that ACTN3 gene polymorphisms does not influence responsiveness to PAPE.